(untitled) (Journal of Guidance and Counselling Studies, 2024)
The study investigated emotional intelligence as correlateof teachers’ job commitment in Public secondary schools in Delta state. The study adopted the correlation survey design. One research question and one hypothesis guided the study. The multi-stage sampling procedure was used to select a sample of 1427 teachers in public secondary schools’. The instruments adopted for data collection were standardized Emotional Intelligence Self-Assessment (EISA) and Job Commitment Questionnaire (JCQ). These instruments were administered using direct delivery approach with the help of regular teachers as research assistants from the sampled schools. The research question raised was answered using Pearson Product Moment Correlation Coefficient (r), while the null hypothesis was tested at 0.05 level of significance using multiple regression analysis. The findings of the study revealed a moderate positive relationship between public secondary school teachers’ emotional intelligence and their job commitment. There was a significant relationship between emotional intelligence scores and job commitment scores of teachers in public secondary schools in Delta State. Based on the findings it was recommended among others that the school system in this regard may have a clear-cut legislation related to pay packages and promotion policy of teachers in public secondary schools in order to improve their level of commitment. There is need to emphasis practices which subsidize and promote emotional intelligence and commitment among secondary school teachers. During recruitment, preference should be given to teachers with high level of emotional intelligence.